2002
DOI: 10.1128/aem.68.10.5151-5154.2002
|View full text |Cite
|
Sign up to set email alerts
|

Double-Staining Method for Differentiation of Morphological Changes and Membrane Integrity of Campylobacter coli Cells

Abstract: We developed a double-staining procedure involving NanoOrange dye (Molecular Probes, Eugene, Oreg.) and membrane integrity stains (LIVE/DEAD BacLight kit; Molecular Probes) to show the morphological and membrane integrity changes of Campylobacter coli cells during growth. The conversion from a spiral to a coccoid morphology via intermediary forms and the membrane integrity changes of the C. coli cells can be detected with the double-staining procedure. Our data indicate that young or actively growing cells are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 13 publications
0
27
0
2
Order By: Relevance
“…The LIVE/DEAD double staining kit (Sigma, St Louis, MO, USA), which allows the simultaneous fluorescence staining of viable (Calcein-AM, excitation 495 nm, emission 515 nm) and dead (Propidium iodide, PI, excitation: 535 nm, emission: 617 nm) cells (41,42), was used. Macrophages J774.2 were seeded in a 96-well plate at a count 8,000 cells/ well and incubated for 24 h with 0.1 mg/ml of coated or uncoated CSNPs.…”
Section: Cell Culture and Cytotoxicity Assaysmentioning
confidence: 99%
“…The LIVE/DEAD double staining kit (Sigma, St Louis, MO, USA), which allows the simultaneous fluorescence staining of viable (Calcein-AM, excitation 495 nm, emission 515 nm) and dead (Propidium iodide, PI, excitation: 535 nm, emission: 617 nm) cells (41,42), was used. Macrophages J774.2 were seeded in a 96-well plate at a count 8,000 cells/ well and incubated for 24 h with 0.1 mg/ml of coated or uncoated CSNPs.…”
Section: Cell Culture and Cytotoxicity Assaysmentioning
confidence: 99%
“…The existence of viable but nonculturable (VBNC) bacteria (13,21,24), which reduce the sensitivity of culture-based assays, has been demonstrated. Analysis of membrane integrity in order to distinguish between viable and dead cells in various bacterial species has been proposed (2,14,17,19); some of these assays are based on double staining combining Syto 9 and propidium iodide (PI) (6,9,26). To date, only three studies dealing with the detection of Legionella cells by flow cytometry have been reported (15,27,29), and none of them analyzed the presence of VBNC cells, which was undertaken in this study.…”
mentioning
confidence: 99%
“…Transcurrido dicho tiempo, se tomó una alícuota de 5 µl y se depositó en un portaobjetos cubierto con poli-L-lisina (SIGMA), se cubrió con un cubreobjetos y se selló con vaselina para evitar la evaporación de la muestra (Alonso et al, 2002) .…”
Section: Recuento De Viables Mediante La Técnica De Tinción Con Fluorunclassified